2003
DOI: 10.1002/mds.10383
|View full text |Cite
|
Sign up to set email alerts
|

Reversible reorganisation of the motor cortical representation of the hand in cervical dystonia

Abstract: Previous work has suggested that there may be a widespread disturbance of motor control mechanisms in patients with cervical dystonia. In the present study, we used transcranial magnetic stimulation to investigate the topography of the corticomotor projection to the abductor pollicis brevis (APB) muscle in 10 subjects with idiopathic torticollis. Threshold-adjusted stimuli were delivered at multiple scalp sites during a low-level voluntary contraction of the APB, and maps were generated of motor evoked potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…This study suggested that changes in the primary motor cortex of dystonic patients might be secondary to abnormal afferent inputs that injected BoNT-A may transiently modulate. A reversible reorganization of the hand motor cortical representation after BoNT-A injections was demonstrated by the same group also in patients with cervical dystonia (Thickbroom et al, 2003) and primary writing tremor (Byrnes et al, 2005).…”
Section: Effects Of Bont-a On Cortical Mechanismsmentioning
confidence: 95%
“…This study suggested that changes in the primary motor cortex of dystonic patients might be secondary to abnormal afferent inputs that injected BoNT-A may transiently modulate. A reversible reorganization of the hand motor cortical representation after BoNT-A injections was demonstrated by the same group also in patients with cervical dystonia (Thickbroom et al, 2003) and primary writing tremor (Byrnes et al, 2005).…”
Section: Effects Of Bont-a On Cortical Mechanismsmentioning
confidence: 95%
“…BTX has been hypothesized to exert additional therapeutic effects by indirectly altering motor afferent feedback to the brain and thereby altering brain activity [7,8]. Empirical evidence for this has been shown in a study in which cortical (gray matter) functional mapping abnormalities known to exist in focal dystonias [9,10] reversed during BTX treatment [11]. In the present study, we sought to determine whether BTX exerts beneficial effects in subcortical motor circuitry, and whether such effects manifest in the white matter of this circuitry.…”
mentioning
confidence: 99%
“…Accordingly, DTI studies have shown normalization of white-matter abnormalities after botulinum toxin treatment in some dystonia patients, 67 and in TMS studies in cervical dystonia patients treated with botulinum toxin, abnormalities in hand motor cortex were reversed. 68 …”
Section: Pharmacologic Treatmentmentioning
confidence: 99%